Utilizing iVariantGuide for Variant Assessment of Next‐Generation Sequencing. Issue 1 (12th February 2019) - Chaudhry, Sophia R.; Tainsky, Michael A.
Abstract: Molecular genetic testing provides the capability for personalized prediction, diagnosis, and pharmacological treatments of disease and disorders. Variant assessment of next‐generation sequencing (NGS) is a crucial component of genetic testing for clinicians to counsel patients on risk and management. The iVariantGuide application is a dynamic Web‐based application made for the tertiary analysis of NGS. Along with variant assessment, iVariantGuide provides a unique interactive pathway impact analysis of genetic variants, as well as a unique Gene Ontology (GO) analysis. Here we provide a step‐by‐step guide on how to utilize iVariantGuide, employing a publicly available NGS dataset consisting of a cohort of germline DNAs from high‐risk serous ovarian cancer (OVCA) patients. The application will be used to exhibit the ease in filtering down to a set of compelling novel variants and their impact on biological pathways and GO terms. © 2019 by John Wiley & Sons, Inc.